2009
DOI: 10.1016/j.wavemoti.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Phononic properties of hexagonal chiral lattices

Abstract: a b s t r a c tThe manuscript reports the outcome of investigations on the phononic properties of a chiral cellular structure. The considered geometry features in-plane hexagonal symmetry, whereby circular nodes are connected through six ligaments tangent to the nodes themselves. In-plane wave propagation is analyzed through the application of Bloch theorem, which is employed to predict two-dimensional dispersion relations as well as illustrate dispersion properties unique to the considered chiral configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
170
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(183 citation statements)
references
References 26 publications
5
170
0
1
Order By: Relevance
“…The size and position of phononic band gaps in cellular solids can be controlled via the topology 13 and dimension 14 of the underlying unit cell. Apart from the chosen geometry 9,15 , the slenderness ratio of the struts 8 and the angle between the struts 16 were identified as key parameters for controlling the band structure.…”
Section: 2mentioning
confidence: 99%
“…The size and position of phononic band gaps in cellular solids can be controlled via the topology 13 and dimension 14 of the underlying unit cell. Apart from the chosen geometry 9,15 , the slenderness ratio of the struts 8 and the angle between the struts 16 were identified as key parameters for controlling the band structure.…”
Section: 2mentioning
confidence: 99%
“…In this work, a representative auxetic structural network with internal rotational units, known as the chiral lattice is investigated with an equivalent, micropolar-continuum model in an attempt to remove the indeterminacy n ¼ À1 encountered so far (Prall and Lakes, 1997;Spadoni, 2008;Spadoni et al, 2009). A detailed microstructural analysis of the chiral lattice is also employed to describe the repercussions of auxetic behavior on the relationship between Young's modulus, shear modulus and Poisson's ratio.…”
Section: Introductionmentioning
confidence: 99%
“…A global stability criterion that purely depends onz was first determined by Maxwell for pin-joined lattices comprising spring-like ligaments 1 , and then modified to account for the nature (pin or welded) of the joints 6 , the bending stiffness of the struts 7,8 , self-stresses 9 , dislocation defects 10 , collapse mechanisms 11 and boundary modes [12][13][14][15] . In recent years, the dynamic response of periodic lattices has also attracted considerable interest [16][17][18][19] because of their ability to tailor the propagation of elastic waves through directional transmissions [20][21][22][23] and bandgaps (frequency ranges of strong wave attenuation) [21][22][23][24] . However, though several studies have shown that the wave propagation properties of periodic lattices are highly sensitive to the architecture of the network [20][21][22][23][24] , a global criterion connecting the frequency and size of bandgaps to the lattice topology is still not yet in place.…”
mentioning
confidence: 99%